Business plan for web based virtual tour in the real estate industry - Del Castillo, Noel E. (University of the Philippines Diliman, 2011)
The Business Concept is about focusing on the technology of Virtual Tour in the real estate industry. Virtual Tour is providing an almost real time experience on the user-end. Real time in a way, it gives the user control on the view and location of a certain tour. At the moment, this is on the integration of 360 Photography and Flash Presentation that can give a basic virtual tour experience to the user. But with an integrated functional website that combines Virtual Tour and other web technologies, it can change the way real estate do their business. Real Estate is the ideal market because the major customers of the Philippine real estate come from Overseas Workers (OFWs). These customers work outside the country which means there's a limitation in transportation. Which is why, the Internet is the ideal place to grab them and Real Estate companies can do that through this Business. The Business is about making money by selling a web-platform website that provides a virtual tour package, and providing services. These services are : Virtual Tour Implementation, Product/Web enhancements, Product/Web Training. The Business is playing in the Information Technology Industry. Like other companies, this business provides solution through web based and software solutions that will cater the need on the real estate industry. Its differentiation factor is that this Business Core Competency is on its Virtual Tour capability along with other useful web technologies like Google and Facebook Integrations.